Accessibility of the Poor to the Rural Water Supply - A Quick Evaluation - Planning Commission (Planning Commission, 1978)
The problem of supply of drinking water has been a formidable one for a long time. During the Fourth Five Year Plan, a bulk of the provision was meant for the areas of acute scarcity and those endemic to water-borne diseases. A Centrally Sponsored Scheme known as the Accelerated Rural Water Supply (ARP) was introduced in 1972-73 to deal with the difficult areas.
Programme Evaluation Organisation Planning Commission